Self-Referential Processing Can Modulate Visual Spatial Attention Deficits in Children With Dyslexia - Zhou, Aibao; Duan, Baojun; Wen, Menglin; Wu, Wenyi; Li, Mei; Ma, Xiaofeng; Tan, Yanggang (Frontiers in Psychology, 2019)
Considerable research has shown that children with dyslexia have deficits in visual spatial attention orienting. Additionally, self-referential processing makes self-related information play a unique role in the individual visual spatial attention orienting. However, it is unclear whether such self-referential processing impacts the visual spatial attention orienting of children with dyslexia. Therefore, we manipulated the reference task systematically in the cue-target paradigm and investigated the modulation effect of self-referential processing on visual spatial attention of children with dyslexia. In the self-referential processing condition, we observed that children with dyslexia demonstrated stable cue effects in the visual spatial attention orienting tasks when the Stimulus Onset Asynchronies (SOAs) were set to 100ms, while other-referential processing weakened the cue effects of the visual spatial attention orienting of children with dyslexia. With cue effect as the index, we also observed that the self-referential processing had a significant larger regulatory effect at the early stage of visual spatial attention orienting, as compared with other-referential processing. These differences exists a high-ranked consistency between children with dyslexia and typically developing reader. The results suggested that self-referential processing can regulate the visual spatial attention deficits of children with dyslexia.